A New Sodium Calcium Cyclotetravanadate Framework: "Zero‐Strain" during Large‐Capacity Lithium Intercalation. (1st October 2021) - Yang, Liting; Liang, Guisheng; Cao, Haijie; Ma, Siyuan; Liu, Xuehua; Li, Xiao; Chen, Guanyu; You, Wenbin; Lin, Chunfu; Che, Renchao
Abstract: "Zero‐strain" materials with little lattice strain and volume change during long‐term cycling are ideal electrode choices for long‐life lithium‐ion batteries. However, the very limited "zero‐strain" materials explored generally show small capacities (< 200 mAh g −1 ), and the origin of "zero‐strain" is still unclear. Here, Na2 Ca(VO3 )4 (NCVO) nanowires are explored as a new anode material capable of keeping single‐phase‐transition "zero‐strain" during large‐capacity (381 mAh g −1 ) Li + intercalation. NCVO owns a crystal structure with isolated [V4 O12 ] 4− tetracycles separated by large‐sized NaO6 octahedra and CaO8 square antiprism decahedra, generating large‐sized quadrilateral and hexagonal channels (≈ 3.6 Å). During lithiation, two‐electron transfer per vanadium is accomplished, introducing a large amount of Li + into interstitial sites and increasing the size of reduced vanadium ions. The former and latter expansion effects are eliminated by the superior volume‐buffering capabilities of the sufficiently large interstitial sites and electrochemical inactive Na‐/Ca‐based polyhedra, respectively, thus achieving "zero‐strain" with the maximum volume variation of only 0.039% and mean strain of only 0.060%. Therefore, the NCVO nanowires exhibit exceptional cyclic stability, as demonstrated by 93.8%/93.2%/94.7% capacity retention over 2000/2000/7000 cycles at 1C/2C/10C. The understanding of the crystal‐structural features for "zero‐strain" provides a guide for the future designs of "zero‐strain" energy‐storage materials. Abstract : Single‐phase‐transition "zero‐strain" and a large reversible capacity (381 mAh g −1 ) harmoniously coexist in a new Na2 Ca(VO3 )4 ‐nanowire Li + ‐storage material. Due to the volume‐buffering capabilities of the large interstitial sites and electrochemical inactive Na‐/Ca‐based polyhedra in Na2 Ca(VO3 )4, its volume variation and lattice strain are the smallest among the explored Li + ‐storage materials, leading to its excellent cyclic stability for thousands of cycles.